Administration of ethanol extract of young papaya seeds (Carica papaya L.) in young adult mice (Mus musculus) causes lower spermatozoa quality compared to control - Satriyasa, Bagus Komang; Amaral, Meriana Barreto; Arijana, IG Kamasan Nyoman; Cahyawati, Putu Nita; Artini, Ayu Putu Satria; Rosyada, Widia Egarani (Edelweiss Applied Science and Technology, 2025)
This study aims to determine whether the ethanol extract of papaya seeds (Carica papaya L.) can affect the quality of spermatozoa in young adult mice (Mus musculus). An experimental study was conducted using a post-test only control group design. The sample consisted of 36 male mice (Mus musculus) of the Swiss Webster strain, aged 2-3 months, with a body weight of 20-30 grams. The mice were divided into two groups: the control group (P0), which included 18 male mice given 3% Tween as much as 0.5 ml, and the treatment group (P1), which included 18 male mice given ethanol extract of young papaya seeds (Carica papaya L.) at a dose of 0.21 mg/gram body weight, administered orally at 0.5 ml for 36 days. The data obtained were analyzed using the independent sample t-test. This study is a laboratory experiment designed to evaluate and examine the significance of young papaya seed extract in affecting spermatozoa quality.